1992
DOI: 10.1007/bf00202105
|View full text |Cite
|
Sign up to set email alerts
|

Structure of densified vitreous silica: Silicon and oxygen XANES spectra and multiple scattering calculations

Abstract: Abstract. The decrease of the mean Si-O-Si angle in vitreous silica upon densification from 2.20 to 2.36 gcm -3 has been followed by oxygen and silicon K-edge XANES spectroscopy. Multiple scattering calculations using clusters of two shells around the oxygen and silicon atoms, respectively, are in good agreement with experimental absorption spectra and confirm mean Si-O-Si angles between 130 and 144 ~ for these samples, and a decrease of the mean angle with densification. The experimental spectra also exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 23 publications
4
42
0
Order By: Relevance
“…This approach is particularly helpful because the connection between x-ray Raman features and the local oxygen electronic bonding environment has not been fully understood in these materials. The x-ray Raman spectra for amorphous SiO 2 glass at 1 atm and MgSiO 3 glass are similar and consist of a broad peak at Ϸ538 eV, consistent with previous studies of the oxygen K-edge spectra of SiO 2 glasses at 1 atm (27,33,34) (Fig. 2 A).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…This approach is particularly helpful because the connection between x-ray Raman features and the local oxygen electronic bonding environment has not been fully understood in these materials. The x-ray Raman spectra for amorphous SiO 2 glass at 1 atm and MgSiO 3 glass are similar and consist of a broad peak at Ϸ538 eV, consistent with previous studies of the oxygen K-edge spectra of SiO 2 glasses at 1 atm (27,33,34) (Fig. 2 A).…”
Section: Resultssupporting
confidence: 75%
“…The low energy feature for pyroxene is probably associated with Mg-O- [4] Si (41). The 538 eV feature in quartz arises from the transition of the core electrons from 1s states to unoccupied oxygen 2p states hybridized with the silicon 3s and 3p states in two nearby [4] Si and that at Ϸ546 eV apparently originates from its long-range periodicity as it becomes prevalent for the larger clusters with several coordination shells in full multiple-scattering simulations (33). (D) Oxygen K-edge spectra for amorphous MgSiO 3 at 1 atm and perovskite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore experiments were conducted below 1000 K. Increasing temperature resulted only in a progressive shift of feature C toward lower energy. Feature C is most likely due in a large part to the EXAFS signal associated with the Si-O pair correlation (Davoli et al, 1992). Then, we attribute the shift in feature C to the presence of a longer average Si-O bond length at higher temperatures thanks to the l/R2 dependence of the EXAFS oscillations (R is the average Si-O distance here).…”
Section: In-situ Melting Of Na2si20 5 Glass To 900 Kmentioning
confidence: 82%
“…In general the conclusion has been reached that either there is little or no coordination change, or it is unquenchable to room pressure: For example, for SiO2 glasses it is has been shown that an increase in pressure up to 30 kbar produces no changes of the Si-O bond-length of the network-forming tetrahedra but produces instead a decrease of the intertetrahedral angles (Seifert et al 1983;Davoli et al 1992). Highly sensitive NMR investigations have identified the presence of several percent of more highly coordinated Si from pressures much higher than those accessed in this work (Stebbins and McMillan 1989;Xue et al 1989).…”
Section: Discussionmentioning
confidence: 99%